What were the drivers of improving child nutritional status in Bangladesh?: an analysis of national household data from 1992 to 2005 guided by the UNICEF framework - Waid, Jillian; Sinharoy, Sheela; Ali, Masum; Alam, Md Mashud; Wendt, Amanda; Gabrysch, Sabine (The journal of nutrition, 2021)
Bangladesh has experienced rapid reductions in child undernutrition and poverty, increases in maternal education, and dietary change over the past 3 decades.We aimed to quantify the determinants of the improvement in child nutritional status among preschool-aged children in Bangladesh from 1992 to 2005.We utilized data from 4 rounds of 2 linked and seasonally balanced survey systems: the Bangladesh Household [Income and] Expenditure Surveys (H[I]ES) and the Child [and Mother] Nutrition Survey (C[M]NS). We analyzed 10,780 children aged 6-59 mo, divided into 2 age groups (6-23 mo and 24-59 mo). We used Blinder-Oaxaca decomposition to assess the impact of changing determinants on nutritional status over time, guided by the UNICEF conceptual framework for the causes of child malnutrition.There were significant improvements in child growth over time for all z-score measures—length/height-for-age (LAZ/HAZ), weight-for-length/height (WLZ/WHZ), and weight-for-age (WAZ)—and in many potential determinants of child growth across domains of the UNICEF framework. Among younger children, decomposition explained 67% of the observed change in LAZ, 130% of WLZ, and 73% of WAZ. Among older children, decomposition explained 41% of the observed change in HAZ and 36% of WAZ. Drivers varied, with improvements in care of children as the only driver in both age groups and for all growth measures. Declines in disease prevalence drove improvements in weight-based measures. For younger children, household diets and household environments were significant drivers of improvement in LAZ and WAZ. For older children, increasing income was the largest driver of HAZ and WAZ.Increasing income did not independently drive improvements for younger children but drove improved growth among children aged 2-4 y. This points to the need to focus on nutrition-specific and nutrition-sensitive interventions to decrease child undernutrition in the vulnerable first 1000 days of life.
Gesehen am 26.05.2021